The role of puberty in experimental pain sensitivity in healthy adolescent girls - Hadas Nahman-Averbuch; Gourav Banerjee; Joel Brown; Alana McMichael; Arbi Ben Abdallah; Sarah Buday; Thomas Baranski; Simon Haroutounian; Deanna Barch; Sarah Garwood; Jacob AuBuchon (PAIN Reports)
Abstract. Introduction:. Puberty is a critical developmental period during which changes in pain sensitivity are observed. Previous studies found that older and more mature adolescents have lower experimental pain sensitivity. However, it is unclear whether the differences in pain sensitivity are due to age or the pubertal maturation effect. Objectives:. This observational study examined the relationships between the pubertal maturation stage, age, and experimental pain sensitivity in healthy girls. Methods:. Healthy adolescent girls (n = 52, mean age 12.0 ± 1.4 years) completed the Pubertal Developmental Scale (PDS) to assess their pubertal stage. In addition, they completed a comprehensive quantitative sensory testing session, including pain thresholds, pain ratings to noxious stimuli, and pain modulation tests. Separate regression models were performed to assess the effect of pubertal maturation and age on experimental pain sensitivity as well as differences in experimental pain sensitivity between girls in different subjective self-perceived pubertal timing relative to peers. Results:. No relationships were found between the PDS score and experimental pain sensitivity; however, age was significantly related to cold pain tolerance (P = 0.030). In addition, to differentiate between puberty and age, experimental pain sensitivity was compared in a subsample of girls of the same age but at different pubertal stages, and no differences in experimental pain sensitivity were observed. No differences were also found when comparing girls who mature early, same, or late relative to their peers. Conclusion:. Puberty and age may have no effect on experimental pain sensitivity in healthy girls.